Amaranth Advisors LLC : anatomy of a hedge fund meltdown - Breslin, Bret; Farivari, Justin; Michalak, Rob; Rasmussen, Carson; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On September 22, 2006, Nicholas Maounis, founder of Amaranth Advisors LLC, reported to investors that his hedge fund had lost approximately 65% of its value (about $6.0 billion of $9.2 billion) since the end of August 2006. His hope was that, despite these losses, he would be able to convince his investors to stay the course and not divest; if they divested, then Amaranth would join the annals of hedge fund history as the largest financial meltdown ever. Looking beyond the local travail of Amaranth to the potential global disruption of the world financial system, how would the situation play out in the long term?
Originally published in Breslin, B., Farivari, J., Michalak, R., Rasmussen, C., & ORourke, J. S. (2007). Amaranth Advisors LLC: Anatomy of a hedge fund meltdown. 07-09. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Amaranth Advisors LLC; Hedge funds; Corporations -- Investor relations